2001
DOI: 10.1016/s0736-0266(01)00004-3
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of gamma radiation sterilized cortical bone allografts

Abstract: Gamma radiation is widely used for sterilization of human cortical bone allografts. Previous studies have reported that cortical bone becomes brittle due to gamma radiation sterilization. This embrittlement raises concern about the performance of a radiation sterilized allograft in the presence of a stress concentration that might be surgically introduced or biologically induced. The purpose of this study was to investigate the effect of gamma radiation sterilization on the fracture resistance of human femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 35 publications
5
79
1
2
Order By: Relevance
“…Although it is known that the gamma radiation sterilization process impairs the mechanical properties of bone allografts [2,4,6,12,22,35,55,66], there has not been a formal investigation, to our knowledge, of the high-cycle fatigue behavior of gamma-irradiated bone at physiologically relevant stress levels. Such information could be useful to gain insight into the extent to which the fatigue life of structural bone allograft may be compromised by gamma radiation sterilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is known that the gamma radiation sterilization process impairs the mechanical properties of bone allografts [2,4,6,12,22,35,55,66], there has not been a formal investigation, to our knowledge, of the high-cycle fatigue behavior of gamma-irradiated bone at physiologically relevant stress levels. Such information could be useful to gain insight into the extent to which the fatigue life of structural bone allograft may be compromised by gamma radiation sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…There was a loss in fatigue life with radiation sterilization because of the damage that occurs to the collagen matrix with irradiation owing to the scission of the peptide backbone of the collagen molecule and others have reported losses in mechanical properties with gamma radiation sterilization [2,4,6,12,22,35,55,66]. Therefore, it was not surprising to find a loss of high-cycle fatigue life between control and gamma-irradiated bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in the application of sterilization doses ranging from 25 to 35 kGy [16], although even at such a "standard dose" the effect of irradiation on the mechanical integrity of bone and tissue is still controversial. For doses up to 35 kGy, several studies [7,8,10,[18][19][20] have reported a significant effect on the post-yield properties of cortical bone, in particular significant reductions in plastic properties such as ultimate strength and work-of-fracture, but little effect on the elastic properties, i.e., stiffness and elastic limit. Conversely, other studies on bones and tendons [9,14,21,22] have claimed no significant reduction in biomechanical properties after similar doses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has successfully been applied for sterilization of bone allografts in orthopedic surgery [6;7]. However, the radiation doses used (25 to 40 kGy) often reduce the mechanical stability of the bone grafts which might cause the implant to fail [8][9][10].…”
Section: Introductionmentioning
confidence: 99%